A Hanafi law manual in the vernacular: Devletoğlu Yūsuf Balıḳesrī's Turkish verse adaptation of the Hidāya-Wiqāya textual tradition for the Ottoman Sultan Murad II (824/1424). (17th April 2017) - Yıldız, Sara Nur
Abstract: This study examines how Devletoğlu Yūsuf Balıḳesrī's versified Hanafi law manual, written in Anatolian Turkish and dedicated to the Ottoman sultan Murad II (d. 855/1451), engages in a complex relationship between the nascent vernacular, Anatolian Turkish, and the Classical Arabic religious textual tradition. Devletoğlu Yūsuf's work, Manẓūm fıḳıh, is a Turkish paraphrase of the Wiqāya, a popular abridgement of the major Hanafi law handbook, the Hidāya, in the form of a mathnawī (verse work of rhymed couplets). Several passages from the "Book on the Affairs of the Qadi" in Devletoğlu Yūsuf's work are analysed in order to gain insight into how the work functions as a normative text in the Classical Hanafi tradition set within a localized context. Furthermore, this study explores how the work expounds upon the benefits of transmitting religious knowledge in the vernacular and justifies the use of Turkish for religious texts by drawing on Hanafi-approved Persian language practices of religious devotion. Of particular interest is how Devletoğlu Yūsuf grounds his argumentation on the rhetorical theories of the Classical Arabic grammarian, ʿAbd al-Qāhir al-Jurjānī.